Using Social Media Data to Assess the Impact of Infertility on French Patients’ Quality of Life: Retrospective Observational Study - Mouna Mael-Ainin; Pierre-Emmanuel Bouet; Paméla Voillot; Joelle Malaab; Manissa Talmatkadi; Stéphane Schück; Nathalie Massin (Journal of Medical Internet Research)
Abstract BackgroundInfertility is defined as the inability to achieve a live birth after 1 year of regular sexual intercourse, affecting 1 in 6 couples in France. The use of assisted reproductive technology (ART) for infertility issues has been steadily increasing in recent years, with in vitro fertilization being the most common type of ART. Infertility is frequently regarded as a significant life crisis for many individuals, potentially leading to depression, anxiety, social isolation, and sexual dysfunction. Couples experiencing infertility demonstrate a high prevalence of negative emotional responses and decreased life satisfaction as a result of infertility and its treatments. Social media have become key tools for finding and disseminating medical information. ObjectiveThis study aims to explore the most discussed topics among patients with infertility and to characterize the impact of infertility and ART on their quality of life (QoL) by analyzing social media data. MethodsThis retrospective observational study includes French messages from patients in France discussing their infertility between 2019 and 2022. A biterm topic model algorithm was applied to identify the topics discussed automatically. A QoL algorithm—based on the EQ-5D and SF-36 (Short Form 36 Health Survey) questionnaires—classified the messages according to 5 dimensions: physical, psychological, activity-related, social, and financial. ResultsAn analysis was conducted on a dataset of 26,919 messages written by 9807 patients. More than 80% (21,900/26,919) of the data were retrieved from 3 main sources: Doctissimo (9281/26,919, 34.5%), BabyCenter.fr (n=6949, 25.8%), and aufeminin.com (n=5670, 21.1%). Among the users who specified their gender (8813/9807, 89.9%), the majority were female (7942/8813, 90.1%) compared to male users (871/8813, 9.9%). The average age was 41 (SD 6.15) years. The most frequently discussed topics were the ART procedures, marked by miscarriages (5671/26,919, 21.1%), ovulation cycle monitoring (5068/26,919, 18.9%), and balancing attempts to conceive with work responsibilities (3476/26,919, 12.9%). In our study, 59% (5786/9807) of users expressed at least 1 impact on their QoL. Patients mainly reported a physical impact (3610/5786, 62.4%), particularly linked to miscarriages (2137/3610, 59.2%). The psychological impact (3020/5786, 52.2%), including fear and anxiety (1818/3015, 60.3%), was also mentioned. The social impact of infertility (n=654/5786, 11.3%)—notably its effects on the couple’s relationship (438/651, 67.3%)—the financial burden of infertility treatments (521/5786, 9%), and the impact on activities (503/5786, 8.7%) were also identified. ConclusionsPatients facing infertility share their experiences on social media. We observed a strong impact on their QoL, affecting their physical and psychological health, as well as their social, financial, and professional lives. These results underline the importance of taking into account the multiple dimensions of infertility when caring for patients and highlight the important role of social media in supporting and understanding this reality.